Diplomasi pertahanan dan perubahan iklim: Studi kasus Indonesia dan Selandia Baru - Rahayu, Dian Diana; Aritonang, Sovian (Jurnal Praksis dan Dedikasi Sosial, 2025)
Defense Diplomacy and Climate Change: A Case Study of Indonesia and New Zealand Climate change has emerged as a significant global security threat, particularly for Pacific and Southeast Asian island nations, including Indonesia and New Zealand. Threats such as rising sea levels, extreme weather events, and resource crises demand a more integrated response through defence diplomacy. This study analyzes the role of defence diplomacy in addressing climate change, focusing on regional cooperation in the Pacific and ASEAN regions. Using a qualitative approach and policy analysis, the research explores New Zealand’s strategies for reducing emissions in the defence sector and its engagement in multilateral forums such as the Pacific Defence Meeting. On the other hand, the study identifies the challenges faced by Indonesia in integrating defence diplomacy with climate change policy, including the implementation of Reducing Emissions from Deforestation and Forest Degradation (REDD+) and the Long-Term Strategy for Low Carbon and Climate Resilience 2050 (LTS-LCCR 2050). The findings highlight the need for integrated cross-national responses to build more resilient regional security against the threats of climate change. Perubahan iklim telah menjadi ancaman keamanan global yang signifikan, terutama bagi negara-negara kepulauan di kawasan Pasifik dan Asia Tenggara, termasuk Indonesia dan Selandia Baru. Ancaman seperti kenaikan permukaan laut, cuaca ekstrem, dan krisis sumber daya menuntut respons yang lebih terpadu melalui diplomasi pertahanan. Studi ini menganalisis peran diplomasi pertahanan dalam menghadapi perubahan iklim dengan fokus pada kerja sama di kawasan Pasifik dan ASEAN. Dengan menggunakan pendekatan kualitatif dan analisis kebijakan, penelitian ini mengeksplorasi strategi Selandia Baru dalam mengurangi emisi sektor pertahanan serta keterlibatannya dalam forum multilateral seperti Pacific Defence Meeting. Di sisi lain, penelitian ini mengidentifikasi tantangan yang dihadapi Indonesia dalam mengintegrasikan diplomasi pertahanan dengan kebijakan perubahan iklim, termasuk implementasi Reducing Emissions from Deforestation and Forest Degradation (REDD+) dan strategi LTS-LCCR 2050. Hasil penelitian menunjukkan bahwa respons lintas negara yang terintegrasi diperlukan guna menciptakan keamanan regional yang lebih tangguh terhadap ancaman perubahan iklim.